Composição centesimal e mineral de plantas alimentícias não convencionais: tupinambor (Helianthus tuberosus), ora-pro-nobis (Pereskia aculeata) e moringa (Moringa oleifera), comercializadas em Porto Belo, Santa Catarina, Brasil (Revista Brasileira de Plantas Medicinais, 2025)
This study aimed to determine the proximal and mineral composition of the unconventional food plants tupinambor (Helianthus tuberosus), ora-pro-nobis (Pereskia aculeata Miller) and moringa (Moringa oleifera Lam), commercialized as flour in the city of Porto Belo – SC. Proximal composition was determined according to the Association of Official Analytical Chemists and the concentration of minerals Fe, Cu, Zn, P, Ca and Mg by atomic absorption spectrometry and K by flame photometry. The results obtained were: moisture (0.88, 0.88 and 0.86 g 100 g-1), ash (16.34, 7.75 and 5.07 g 100 g-1), lipids (3.27, 5.57 and 0.48 g 100 g-1), protein (22.41, 24.79 and 6.53 g 100 g-1), carbohydrates (57.10, 62.02 and 87.06 g 100 g-1) e food fiber (55.39, 48.21 and 19.68 g 100 g-1). According to ANVISA Ordinance n°27, moringa and ora-pro-nobis flours present high protein content and all evaluated flours have high food fiber content. The average results obtained indicate that, except for iron, all samples show significant differences (p